Ethnic profiling in the European Union: pervasive, ineffective, and discriminatory (Open Society Inst.)
Pervasive use of ethnic and religious stereotypes by law enforcement across Europe is harming efforts to combat crime and terrorism, according to this report released by the Open Society Justice Initiative. Ethnic profiling occurs most often in police decisions about who to stop, question, search, and, at times, arrest. Yet there is no evidence that ethnic profiling actually prevents terrorism or lowers crime rates. Throughout Europe, minorities and immigrant communities have reported discriminatory treatment by the police. From massive data mining operations to intimidating identity checks, ethnic profiling is often more of a public relations stunt than a real response to crime. The report, Ethnic Profiling in the European Union: Pervasive, Ineffective, and Discriminatory, details widespread profiling in France, Germany, Italy, The Netherlands, and other EU member states.--Publisher description